P007: Association between serum biomarkers and frailty level in seniors with minor injurys. (2nd June 2016) - Allain-Boulé, N.; Lebon, J.; Sirois, M.; Aubertin-Leheudre, M.; Émond, M.
Abstract : Introduction: Frailty is associated with mobility & physical impairment in seniors with minor injuries. Serum biomarkers have also been suggested as potential markers of these impairments in clinical studies. No study has examined if serum biomarkers could contribute to the diagnosis of frailty in seniors with minor injuries.Objectives: To explore the association between several serum biomarkers (Ferritin, Creatinine, Vitamin D, Albumin, Glucose, Estradiol, Testosterone, Thyroid Stimulating Hormone (TSH), Insulin-Growth Factor (IGF-1) C-reactive protein (CRP)) and frailty level in seniors treated in emergency department (ED) for minor injuries.Methods: Cross-sectional study within the larger CETI cohort. It includes 142 seniors discharged home from 4 EDs after treatment of minor injuries. Their frailty status was measured by the Canadian Study of Health & Aging-Clinical Frailty Scale (CSHA-CFS). Biomarkers were obtained from blood samples. Pearson's correlations (r) were performed to examine the relation between serum biomarkers and frailty levels. Partial correlation controlled for age and sex, were also performed.Results: Due to inclusion criteria, no patient was severely frail. Overall, these preliminary analyses seem to indicate that robust patients tended to have lower Glucose & Vitamin D levels (-0.264 ≤ r ≤ -0.230; p < 0.05), higher Estradiol (r = 0, 230; p < 0.05) & Testosterone (r = 0, 295; p < 0.05), while prefrail/frail patients tended to have higher Glucose & Vitamin D levels (0, 235 ≤ r ≤ 0, 238; p < 0.05), lower Estradiol levels (r = -0, 235; p < 0.05) & more elevated Ferritin levels. Due to the small number of patients, controlling for age and sex lead to non-significant results of the most associations.Conclusion: Pre-frail/frail seniors presenting to EDs with minor injuries tend to have higher Ferritin, Glucose & Vitamin D levels as well as lower sexual hormones levels than robust individuals. Larger samples are needed in order to elucidate which biomarkers could be most useful to identify frail seniors needing clinical attention and to assess a possible association with mobility impairments in this population.